Effect of Hot Burnishing Aided by Infrared Radiation on the Modification of Surface and Subsurface of AISI 1045 Steel - Sanchez, L. E.A. [UNESP] (2017)
The burnishing occurs by plastic deformation by rearranging the excess of material on the surface peaks to its valleys. In order to improve the process, a laser can be used as a heating source to reduce the material yield stress. However, this technique is expensive and the heating apparatus requires space around the machine tool. In this context, this work proposes the study of a low cost heating source made of quartz electrical resistance. The quartz electrical resistance emits infrared radiation and produces temperatures around 210 Celsius Degrees on the workpiece surface. To verify the applicability of this technique, the results were compared with the conventional burnishing process using AISI 1045 steel with a burnishing tool that was specially designed for the test. The surface roughness, circularity, microhardness and residual stress were analyzed as output variables for different values of force, rotational speed, and number of passes. Results showed that the thickness of the workpieces subsurface layer under hot burnishing was larger and with more strain hardening characteristics when compared with the conventional burnishing. After the turning process, the workpieces presented tensile residual stress. Using the hot burnishing, the workpieces start presenting compressive stress just after the first pass, while in conventional burnishing compressive stress was only observed after the second pass and with lower values, about the half. Both surface roughness and circularity deviation were not improved by hot burnishing.